Induction of the CLOCK gene by E2-ERα signaling promotes the proliferation of breast cancer cells. - Liyun Xiao; Alan K Chang; Ming-Xi Zang; Hailian Bi; Shujing Li; Miao Wang; Xinrong Xing; Huijian Wu (PLoS ONE)
Growing genetic and epidemiological evidence suggests a direct connection between the disruption of circadian rhythm and breast cancer. Moreover, the expression of several molecular components constituting the circadian clock machinery has been found to be modulated by estrogen-estrogen receptor α (E2-ERα) signaling in ERα-positive breast cancer cells. In this study, we investigated the regulation of CLOCK expression by ERα and its roles in cell proliferation. Immunohistochemical analysis of human breast tumor samples revealed high expression of CLOCK in ERα-positive breast tumor samples. Subsequent experiments using ERα-positive human breast cancer cell lines showed that both protein and mRNA levels of CLOCK were up-regulated by E2 and ERα. In these cells, E2 promoted the binding of ERα to the EREs (estrogen-response elements) of CLOCK promoter, thereby up-regulating the transcription of CLOCK. Knockdown of CLOCK attenuated cell proliferation in ERα-positive breast cancer cells. Taken together, these results demonstrated that CLOCK could be an important gene that mediates cell proliferation in breast cancer cells.